PERAN KEGIATAN EKSTRAKURIKULER DALAM MEMBENTUK PERILAKU POSITIF SISWA SEKOLAH DASAR NEGERI 13/I MUARA BULIAN - Nabilla Najwa Azzahra; Silvina Noviyanti (STKIP Subang, 2026)
Extracurricular activities serve as an essential medium for developing students' potential and character in elementary schools. This research aims to describe the role of extracurricular activities in forming positive behavior among students at SD Negeri 13/I Muara Bulian. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving extracurricular teachers and students participating in drum band and sports activities. The findings reveal that extracurricular activities significantly contribute to enhancing students' discipline, responsibility, cooperation, and self-control. Student participation in these structured activities effectively channels their high energy into positive outlets, resulting in more conducive behavioral changes within the school environment. This research demonstrates that extracurricular activities can be utilized as an effective educational approach for character building and positive behavior development in elementary school students, proving their strategic importance beyond merely complementing the academic curriculum.